Comparison of pyloromyotomy, pyloric buginage, and intact pylorus on gastric drainage in gastric pull-up surgery after esophagectomy - Gholamreza Mohajeri (Journal of Research in Medical Sciences, 2016)
Background: There are controversies regarding the usefulness of the pyloric drainage methods after esophagectomy as well as differences among various pyloric drainage techniques. Therefore, we compared the outcome of pyloromyotomy, pylorus buginage, and no intervention methods on gastric emptying among patients undergone esophagectomy. Materials and Methods: In this randomized clinical trial, patients with diagnosed esophageal cancer or any other benign lesions candidate for esophagectomy were selected. They randomized in three groups with three different approaches for gastric pull-up esophageal surgery including esophagectomy with pyloromyotomy, esophagectomy without intervention, and esophagectomy with pylorus buginage. The outcomes of procedures regarding gastric emptying time and delayed gastric emptying were compared. Results: Thirty patients were allocated in three groups. Gastric emptying time was not significantly different in the three groups (P > 0.05). Frequency of delayed gastric emptying, complications and barium leakage were not different in three studied groups (P > 0.05). Conclusion: Gastric emptying time and delayed gastric emptying were not different between common pyloric drainage methods after esophagectomy and esophagectomy without drainage.